The complete chloroplast genome sequence of the relict woody plant Metasequoia glyptostroboides Hu et Cheng - Chen, Jinhui; Hao, Zhaodong; Xu, Haibin; Yang, Liming; Liu, Guangxin; Sheng, Yu; Zheng, Chen; Zheng, Weiwei; Cheng, Tielong; Shi, Jisen (Frontiers in Plant Science, 2015)
Metasequoia glyptostroboides Hu et Cheng is the only species in the genus Metasequoia Miki ex Hu et Cheng, which belongs to the Cupressaceae family. There were around ten species in the Metasequoia genus, which were widely spread across the Northern Hemisphere during the Cretaceous of the Mesozoic and in the Cenozoic. M. glyptostroboides is the only remaining representative of this genus. Here, we report the complete chloroplast (cp) genome sequence and the cp genomic features of M. glyptostroboides. The M. glyptostroboides cp genome is 131,887 bp in length, with a total of 117 genes comprised of 82 protein-coding genes, 31 tRNA genes and four rRNA genes. In this genome, 11 forward repeats, nine palindromic repeats and 15 tandem repeats were detected. A total of 188 perfect microsatellites were detected through simple sequence repeat (SSR) analysis and these were distributed unevenly within the cp genome. Comparison of the cp genome structure and gene order to those of several other land plants indicated that a copy of the inverted repeat (IR) region, which was found to be IR region A (IRA), was lost in the M. glyptostroboides cp ge-nome. The five most divergent and five most conserved genes were determined and further phylogenetic analysis was performed among plant species, especially for relat-ed species in conifers. Finally, phylogenetic analysis demonstrated that M. glyptostro-boides is a sister species to Cryptomeria japonica (L. F.) D. Don and to Taiwania cryptomerioides Hayata. The complete cp genome sequence information of M. glyp-tostroboides will be great helpful for further investigations of this endemic relict woody plant and for in-depth understanding of the evolutionary history of the conif-erous cp genomes, especially for the position of M. glyptostroboides in plant systemat-ics and evolution.